Field investigation of the bearing behavior of grouted gravel pile composite foundations in Karst Terrain - Lingzhi Zhang; Changhe Yan; Chunyong Jiang (PLoS ONE, 2026)
The extensive underlying karst in southwestern and southern China presents significant challenges for deformation control in railway and highway subgrades. This paper proposes an integrated technology combining grouted gravel piles with the treatment of underlying karst dissolution fractured zones, along with the requisite construction machinery and procedural sequence. The technology is implemented and validated through a railway subgrade project, involving a series of field investigations. The grouting-induced improvement mechanism in the surrounding soil is revealed through the evolution of lateral earth pressure and pore water pressure. The bearing behavior and load-transfer mechanism of a single pile are characterized by load-settlement curves, the distributions of axial force and shaft friction, and the load-sharing ratio. Finally, the effectiveness of this technology for the composite foundation is confirmed by field performance data under embankment loading, including settlements at the pile head and various soil depths, stress distributions on pile heads and adjacent soils, pore water pressures at different depths, and lateral displacements at the embankment toe.